Herbal remedies for hypothyroidism: A systematic review and meta-analysis - Fatemeh Ghaffari-Saravi; Assie Jokar (Babol University of Medical Sciences, 2025)
Background: Combination of various medical schools with modern medicine is one of the appropriate methods for diagnosing and treating diseases. Considering the expanded use of herbal remedies, this study aimed to investigate herbal remedies for hypothyroidism. Methods: Keywords related to medicinal plants and hypothyroidism were searched among titles and abstracts of papers published on PubMed, Web of Science, and Scopus to find relevant papers published until the end of 2022. The quality of the extracted papers was assessed using JADAD scale. The data collected from the papers included general information, demographic characteristics of the participants, sample size in each group, type and duration of the intervention, doses of the herbs or extracts, side effects, and the effects of the intervention on thyroid function tests. The I2 index was used to measure the heterogeneity of the papers; if I2 statistic was above 50% or under 50%, the results of the papers were combined using random effect or fixed effect methods, respectively. Results: Five of the 301 papers extracted from the abovementioned databases were selected for systematic review and 4 for meta-analysis. Three of the papers were about the properties of Nigella sativa. The meta-analysis results showed that herbal medicines used in these papers significantly changed level of T4 (SMD=0.86 CI95%: 0.47-1.24), T3 (SMD=0.50 CI95%: 0.13-0.87), and TSH (SMD=-1.19 CI95%: -1.82-0.56) compared to placebo. Conclusions: Herbal medicines improved the results of thyroid function tests; their effects on TSH, T3, and T4 were strong, moderate, and mild, respectively.